Molecular detection of enterovirus D68 among children with acute respiratory tract infection in Ghana - Joyce A. Kubi; Mohamed Mutocheluh; Joseph H.K. Bonney; William K. Ampofo; John K. Odoom (AOSIS, 2019)
Background: Acute respiratory tract infections of viral origin remain a leading cause of morbidity, mortality and economic loss regardless of age or gender. A small number of acute respiratory tract infection cases caused by enterovirus D68 (EV-D68) have been reported regularly to Centers for Disease Control and Prevention since 1987 by countries in North America, Europe and Asia. However, in 2014 and 2015, the number of reported confirmed EV-D68 infections was much greater than in previous years. The National Influenza Centre (NIC), Ghana carries out surveillance of respiratory infections, focusing on those caused by influenza virus; however, there is inadequate information on other viruses causing respiratory infections in Ghana, including EV-D68. Objectives: To investigate the association of EV-D68 with Severe Acute Respiratory Infections (SARI) and Influenza-Like Illness (ILI) in Ghana. Methods: This was a retrospective cross-sectional study which involved archived human respiratory specimens stored at -80 °C at the NIC from 2014 to 2015. Using a random sampling method, oropharyngeal and nasopharyngeal swabs from patients with SARI and ILI that were negative by real-time PCR for human influenza viruses were screened for EV-D68 using real-time reverse transcription-polymerase chain reaction (rRT-PCR). Results: Enterovirus D68 was detected in 4 (2.2%) out of 182 SARI samples tested. EV-D68 was detected in children younger than 5 years (4 - 100% of positives) and was not detected in children older than 5 years. Enterovirus D68 was detected more frequently in SARI cases (3%) than in ILI cases (1.2%). Conclusion: This study has shown for the first time the presence of EV-D68 in acute respiratory infections in Ghana. The results confirmed minimal EV-D68 circulation in the Ghanaian population.